Peningkatkan Keterampilan Berwudhu dengan Menggunakan Metode Demogram Terhadap Anak Usia 5-6 Tahun - Riska Aprilianti (Saliha, 2019)
This research aims to describe the result of demogram method can increase wudhu competent for young children. Method of this study is classroom action research. The data were collected through a questionnaire, interviews, and observation. Subject of this research are Group B in Tk Bina Insan Mandiri. The data were analized by using the qualitative and quantitative. The results showed an increase in the wudhu competent. On initial conditions of indicator 1, over cicle I increase 13,33%. On the cycle II increase 40 %, and cycle III increase 76,92%. Indicator 2, cycle I increase 33,33 %, cycle II increase 40%, and cycle III increase 90,29%. Indicator 4, first is having done facial wash increase 84,62%. Indicator 5 increase significantly up to 100%. Indicator 6, cycle I is 13,33, cycle II is 46,67, amd cycle III 92,30%. Indicator 7, cycle I is 0%, cycle II is 46,67%, dan 76,92% on the cycle III. Indicator 8, cycle I is 6,67%, on cycle II is 40%, and cycle III increase significantly 100%. Indicator 9, cycle I is 13,33%, cycle II increase 26, 67%, and cycle III increase up to 76,92%.